Internally Displaced People and Mental Health Issues - Njiru, Lucy Njarui (Notion Press, 2021)
Reports from many parts of the world have shown an increase in mental health burden across all ages. The impacts of mental health on global development goals have led to mental health inclusion in the Sustainable Development Goals Despite the high number of individuals needing mental health care services, access to these services remains a challenge in many low and middle-income countries. Evidence has shown that the situation is worse among internally, displaced people (IDPs) in comparison to their counterparts. Effective treatment for mental, psychological, and emotional problems is minimally costed. Despite this, treatment coverage for these illnesses remains low across all populations. This chapter provides a brief overview of mental health concerns among IDPs Clinical presentation of common psychiatric conditions among IDPs is examined to provide readers with an enhanced foundation for understanding these conditions. Assessment of mental health is a crucial component since it lays a basis for treatment and intervention planning. Hence, assessment in mental health has also been discussed in this chapter. In addition, the main risk and protective factors for post-traumatic stress disorder (PTSD) have been examined to help plan for effective prevention programmes. Finally, we will present some of the most effective treatment modalities for post-traumatic stress disorder that can be used in managing PTSD among IDPs.
Displacees and Health: Issues and Challenges
Book Chapter; pg. 65
Keywords: Mental Health, Internal Displaced People, Risk and Protective Facts, Posttraumatic Stress Disorder (PTSD)